Bibliometric Analysis on Islamic Microfinance - Judijanto, Loso; Setiyawan, Heri (Westscience Press, 2025)
This study presents a comprehensive bibliometric analysis of Islamic microfinance literature, aiming to map its intellectual structure, thematic evolution, and global collaboration patterns. Using data extracted from the Scopus database and analyzed with VOSviewer, a total of relevant publications from 2000 to 2024 were examined through keyword co-occurrence, temporal overlay, density visualization, co-authorship networks, and country collaborations. The results reveal that Islamic microfinance, poverty alleviation, and financial inclusion are the central themes, while emerging topics such as Islamic social finance, waqf, zakat, and fintech reflect a shifting research focus toward ethical innovation and digital integration. Temporal analysis shows a gradual evolution from early concerns with institutional structures and Shariah compliance toward contemporary discussions on impact and sustainability. The co-authorship and collaboration maps highlight Malaysia and Indonesia as key contributors, with increasing cross-border partnerships involving both Muslim and non-Muslim-majority countries. Despite the growing body of literature, the field remains fragmented in certain areas, with limited research on behavioral dimensions, governance models, and long-term impact assessment. This study contributes to a deeper understanding of the research landscape and offers strategic directions for scholars, policymakers, and practitioners to advance Islamic microfinance as a tool for inclusive and sustainable development.